Determining Urban Development Orientation Based on Air Pollution Diffusion Modeling from Thermal Power Plants, Case Study: Mashhad - mohammadamir moharreri; kamran lari; foroozan arkian; gholamreza salehi (تحقیقات کاربردی علوم جغرافیایی)
There are several limiting factors to the development of cities. These factors lead cities to develop in certain directions. Air pollution as a major problem of metropolises can itself be considered as a limiting factor of urban development by urban decision makers. 4 relatively large power plants are operating in Mashhad. There are currently two power plants in the east of the city and two in the west of Mashhad. Most of the fuel in these power plants is gasoline and natural gas. Modeling the air pollutant emissions of these power plants and identifying the pattern of pollutant emissions across the city can play a key role in the quality of life and health of approximately 3.5 million Mashhad residents. The outputs of this model can also be used as an effective parameter in estimating the urban development model. In this study, the emission of NOX, CO and 10PM pollutants was modeled and evaluated using AERMOD software in Mashhad. Using Arc GIS software, the population affected by these air pollutants was determined by one year solar time, the concentration of pollutants in different areas of the city and the area affected by the pollution concentration range was determined.